2019
DOI: 10.1038/s41388-019-0936-x
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic inactivation of the splicing RNA-binding protein CELF2 in human breast cancer

Abstract: Human tumors show altered patterns of protein isoforms that can be related to the dysregulation of messenger RNA alternative splicing also observed in transformed cells. Although somatic mutations in core spliceosome components and their associated factors have been described in some cases, almost nothing is known about the contribution of distorted epigenetic patterns to aberrant splicing. Herein, we show that the splicing RNA-binding protein CELF2 is targeted by promoter hypermethylation-associated transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 24 publications
1
38
0
Order By: Relevance
“…Our results above indicated that CRNDE inhibited the expression of CELF2, an important tumor suppressor in several cancer types 44 46 . However, the implication of CELF2 in HCC has not yet been well understood to date.…”
Section: Resultssupporting
confidence: 61%
“…Our results above indicated that CRNDE inhibited the expression of CELF2, an important tumor suppressor in several cancer types 44 46 . However, the implication of CELF2 in HCC has not yet been well understood to date.…”
Section: Resultssupporting
confidence: 61%
“…WARS may partially promote the growth of UM cells by activating the PI3K/AKT signaling pathway, thereby accelerating tumor development [44]. In addition to EDNRB and WARS, the remaining 19 genes showing evidence interacting in the progress of various types of cancer [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68], but left few traces showing the connection with UM prognosis in the previous research. https://doi.org/10.1371/journal.pone.0242263.g004…”
Section: Plos Onementioning
confidence: 99%
“…Previous studies reported that SRSF1 is up-regulated in varies types of human tumors, including colon, thyroid, breast, kidney, small intestine and lung cancers 30 − 31 . Piqué et al 32 reported that the splicing RNA-binding protein CELF2 is targeted by promoter hypermethylation-linked transcriptional silencing in the breast cancer. Duan et al 32 suggested the aberrant splicing variants in renal cell cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Piqué et al 32 reported that the splicing RNA-binding protein CELF2 is targeted by promoter hypermethylation-linked transcriptional silencing in the breast cancer. Duan et al 32 suggested the aberrant splicing variants in renal cell cancer. AS was also found to regulate some apoptotic genes.…”
Section: Discussionmentioning
confidence: 99%